2019
DOI: 10.1002/for.2583
|View full text |Cite
|
Sign up to set email alerts
|

A Bayesian structural model for predicting algal blooms

Abstract: A Bayesian structural model with two components is proposed to forecast the occurrence of algal blooms, multivariate mean‐reverting diffusion process (MMRD), and a binary probit model with latent Markov regime‐switching process (BPMRS). The model has three features: (a) forecast of the occurrence probability of algal bloom is directly based on oceanographic parameters, not the forecasting of special indicators in traditional approaches, such as phytoplankton or chlorophyll‐a; (b) augmentation of daily oceanogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 47 publications
(54 reference statements)
0
1
0
Order By: Relevance
“…Sensitivity and precision are as important as accuracy in predicting algal bloom occurrence. This is because high sensitivity and precision can provide indicators that can prevent massive property damage [14][15][16][17]. The elements of the marine environment that cause algal blooms are generally known, but no study 2408 can be found to analyze the influence of each element on algal blooms and predict algal blooms.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity and precision are as important as accuracy in predicting algal bloom occurrence. This is because high sensitivity and precision can provide indicators that can prevent massive property damage [14][15][16][17]. The elements of the marine environment that cause algal blooms are generally known, but no study 2408 can be found to analyze the influence of each element on algal blooms and predict algal blooms.…”
Section: Introductionmentioning
confidence: 99%